Successive passaging through an apple host of six low-virulent Neonectria ditissima isolates increased virulence in one of them - Scheper, Reiny W.A.; Fisher, Brent M.; Bowen, Joanna K.; Amponsah, Nicholas T.; Hedderley, Duncan I. (New Zealand Plant Protection, 2019)
Neonectria ditissima is a serious pathogen of apple. Low-virulent cultures of this fungus have been isolated from cankers, but how and why low-virulent isolates can infect apple is unknown. Rasp wounds on ‘Royal Gala’ trees were inoculated with agar plugs from six low-virulent N. ditissima isolates in a glasshouse. Neonectria ditissima was re-isolated 10 weeks after inoculation. Agar plugs from the re-isolated cultures were used to inoculate ‘Royal Gala’ trees again. After the second re-isolation, conidial suspensions of the original cultures and the 2 x 6 re-isolates were used to determine the virulence on ‘Royal Gala’ compared with field-collected conidia. Three cultures did not cause any lesions; neither did their re-isolates. The re-isolates of two cultures did not differ in virulence compared with the originals. However, the virulence of one isolate increased with each re-isolation, with the second re-isolation causing significantly more lesions, lesion development occurring faster and the lesions being larger than those caused by the original isolate. Therefore, the virulence of N. ditissima isolates can change over time, with loss or gain possibly being attributed to epigenetic and/or genetic changes in the genome.